Production and characterization of monoclonal antibodies against recombinant ORF 049L of rock bream iridovirus. Issue 12 (December 2016) - Li, Qiang; Wang, Youjuan; Zhang, Mingming; Li, Ruijun; Ye, Shigen; Li, Hua
Graphical abstract: Highlights: The open reading frame ( ORF ) 049L of the rock bream iridovirus (RBIV) transmembrane domain was cloned and subjected to recombinant expression. Eight monoclonal antibodies (mAbs) against recombinant ORF 049L were developed. Three selective mAbs were sensitive to RBIV-infected rock bream. Abstract: Iridovirus has been detected in more than 20 fish species, caused severe systemic diseases. Rock bream iridovirus (RBIV) is a known causative agent of epizootics in cultured Oplegnathus fasciatus in China. In this study, monoclonal antibodies (mAbs) against the recombinant RBIV protein ORF 049L were employed to further elucidate the pathogenesis of the virus. Briefly, mAbs against recombinant ORF 049L were prepared. Western blot analysis was performed to assess the ability of the mAbs to bind to the recombinant protein, and the sensitivity of mAbs to RBIV-infected rock bream was analyzed by dot blot analysis, an indirect immunofluorescence assay, and one-step PCR analysis. Eight mAbs against recombinant ORF 049L were developed, of which three (3F8, 2H11, and 2B7) were sensitive to RBIV-infected rock bream. These mAbs provide useful tools to analyze the location and replication in vivo of structural and functional proteins, and the pathogenesis of RBIV in aquatic organisms.